Conversion Of Intuitionistic Fuzzy Muller Automata Into Construct Transition Intuitionistic Fuzzy Muller Automata (Journal of Namibian Studies : History Politics Culture, 2023)
In this paper, Inspired by the intuitionistic fuzzy language as intuitionistic fuzzy Buchi automata, a new approach is proposed as the Muller automata into Transition Muller (Buchi) automata.